The corporate social contract : from enlightened monarch to accountable democarcy : CSR and sovereignty - Paschke, Sasha Uwe Pieter Heinz (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Public Management and Planning))--University of Stellenbosch, 2006.